ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA BERDASARKAN HERZBERG TWO FACTORS THEORY PADA GURU DI SEKOLAH LUAR BIASA NEGERI SEMARANG - Fitriani Nurahmah; Ekawati Ekawati; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Job satisfaction is a result of a person's perception or assumption of how well a job provides important value for their survival and well-being. According to Herzberg Two Factor Theory, job satisfaction was influenced by two factors, it called motivation and maintenance factors. The discrepancy in the ratio of the number of teachers and students, as well as the rolling system carried out across levels and levels, caused job dissatisfaction of teachers in SLB Negeri Semarang. The purpose of this research is analyze the effect or influence of motivation factor and maintenance factor on job satisfaction on teachers in SLB Negeri Semarang. The type of this research is used quantitative method by using a cross-sectional study. The population in this research were 60 teachers of PNS in SLB Negeri Semarang. The sample that used in this research was 60 teachers with total sampling technique. The instrument in this research was used Minnesota Satisfaction Questionnaire (MSQ) to assess job satisfaction and Job Descriptive Index (JDI) questionnaire to assess motivation and maintenance factors. The statistical analysis that used is binary regression test. The results showed that there was no influence motivation factors on job satisfaction (-value=0.065). There is an influence maintenance factors on job satisfaction (-value=0.001). Researchers suggest to increasing motivation factors by improving the promotion system, and providing awards for outstanding teachers. Moreover, improving maintenance factors is also needed by improving working conditions and supervision in SLB Negeri Semarang.